Molecular and immunological characterisation of Theileria parva stocks which are components of the Muguga cocktail used for vaccination against East Coast fever in cattle - Bishop, Richard P.; Geysen, D.; Spooner, P.R.; Skilton, Robert A.; Nene, Vishvanath M.; Dolan, T.T.; Morzaria, S.P. (Elsevier, 2001)
The 'Muguga cocktail' which is composed of three Theileria parva stocks Muguga. Kiambu 5 and Serengeti-transformed has been used extensively for live vaccination against East Coast fever in cattle in eastern, central and southern Africa. Herein we describe the molecular characterization of the T. parva vaccine stocks using three techniques, an indirect fluorescent antibody test with a panel of anti-schizont monoclonal antibodies (Mab). Southern blotting with four T. parva repetitive DNA probes and polymerase chain reaction (PCR)-based assays detecting polymorphism within four single copy loci encoding antigen genes. The Muguga and Serengeti-transformed stocks exhibited no obvious differences in their reactivity with the panel of Mabs, whereas Kiambu 5 differed with several Mabs. Kiambu 5 DNA was very distinct from the Muguga and Serengeti-transformed isolates in the hybridization pattern with all four nucleic acid probes, whereas Muguga and Serengeti-transformed isolates exhibited minor differences and could not be discriminated with one of the probes. PCR amplification in combination with restriction fragment length polymorphism analysis indicated that Kiambu 5 was also markedly divergent from the Muguga and Serengeti-transformed stocks within two of the four antigen coding genes. The T. parva Serengeti-transformed stock did not contain a 130 base pair insert within the p67 sporozoite antigen gene, which has been observed previously in most T. parva parasites isolated from buffalo, and could not be discriminated from T. parva Muguga at any of the four single copy loci. Collectively the data indicate that two of the cocktail components T. parva Serengeti-transformed and Muguga are genetically closely related, while the third component Kiambu 5 is quite distinct. Based on the findings, there may be a need to include only one of the T. parva Muguga and Serengeti-transformed components in the immunizing cocktail. The study demonstrates the value of molecular characterization data for monitoring of live vaccines.